2013
DOI: 10.1142/s0219633613500028
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Predicting the Glass Transition Temperature of Vinyl Polymers by Using Hybrid Pso-SVR Method

Abstract: Based on four physicochemical descriptors (the rigidness descriptor R OM resulted by hydrogenbonding moieties group and/or rings, the chain mobility n, the molecular average polarizability and the net charge of the most negative atom q À Þ derived from the polymers' monomers structure, the support vector regression (SVR) approach combined with particle swarm optimization (PSO), is proposed to construct a model for prediction of the glass transition temperature T g of three classes of vinyl polymers, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Their SVM simulation demonstrated that the concrete ultrasonic pulse velocity was the most effective parameter in improving the accuracy of estimations. SVM models have been used to predict various other material properties such as ionic conductivities, [ 106,107 ] glass transition temperatures, [ 108–110 ] catalyst active sites [ 111 ] and adsorption energies, [ 112 ] and various other properties of innovative materials. [ 113,114 ] [1ni=1nmax(0,1goodbreak−yi(βTxibadbreak−b))]badbreak+λβ2\[\left[ {\frac{1}{n}\mathop \sum \limits_{i = 1}^n \max \left( {0,1 - {y_i}\left( {{\beta ^T}{x_i} - b} \right)} \right)} \right] + \lambda \parallel \beta {\parallel ^2}\] …”
Section: Data‐intensive Strategies and Algorithms For Innovative Mate...mentioning
confidence: 99%
See 2 more Smart Citations
“…Their SVM simulation demonstrated that the concrete ultrasonic pulse velocity was the most effective parameter in improving the accuracy of estimations. SVM models have been used to predict various other material properties such as ionic conductivities, [ 106,107 ] glass transition temperatures, [ 108–110 ] catalyst active sites [ 111 ] and adsorption energies, [ 112 ] and various other properties of innovative materials. [ 113,114 ] [1ni=1nmax(0,1goodbreak−yi(βTxibadbreak−b))]badbreak+λβ2\[\left[ {\frac{1}{n}\mathop \sum \limits_{i = 1}^n \max \left( {0,1 - {y_i}\left( {{\beta ^T}{x_i} - b} \right)} \right)} \right] + \lambda \parallel \beta {\parallel ^2}\] …”
Section: Data‐intensive Strategies and Algorithms For Innovative Mate...mentioning
confidence: 99%
“…Key to the efficient use of ML in the field of chemical materials is the “descriptor selection” tool, which takes the entire descriptor set as an input, or combines it into a new reduced, but more reliable, descriptor set through correlation analysis while providing a mapping to a key performance indicator (KPI) fingerprint. [ 50 ] In this section, the strategy of transforming material data to ML through descriptors is introduced; descriptors can be divided into five main types: constitutional descriptors; [ …”
Section: Key Descriptors Bridging Data‐intensive Discoveries and Expe...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] Support vector machine (SVM), which is a widely used machine learning algorithm, was used to predict ionic conductivity [ 13 ] and glass transition temperatures. [ 14–16 ]…”
Section: Introductionmentioning
confidence: 99%
“…They proved that both the predictive accuracy and generalization ability of SVR are superior to those of the quantitative structure-property relationship (QSPR) model [39]. In 2013, Pei et al [40] used the particle swarm optimization-support vector regression (PSO-SVR) method to predict the T g of three classes of vinyl polymers, and found that PSO-SVR achieves better perfor-mance than the spectral structure-activity relationship analysis and ANN. Furthermore, Alzghoul et al [41] used several machine learning methods including MLR, partial least-squares, principal component regression, ANN and SVR, for the T g prediction of drugs, among which SVR gives the best result with RMSE of 18.7 K. Above all, machine learning based methods have achieved good prediction performance for T g values of many kinds of organic glasses, but few references on using machine learning methods to predict the T g of inorganic glasses are located.…”
Section: Introductionmentioning
confidence: 99%